2013
DOI: 10.1242/jcs.132852
|View full text |Cite
|
Sign up to set email alerts
|

Gα73Β is a downstream effector of JAK/STAT signalling and a regulator of Rho1 inDrosophilahaematopoiesis

Abstract: JAK/STAT signalling regulates many essential developmental processes including cell proliferation and haematopoiesis, whereas its inappropriate activation is associated with the majority of myeloproliferative neoplasias and numerous cancers. Furthermore, high levels of JAK/STAT pathway signalling have also been associated with enhanced metastatic invasion by cancerous cells. Strikingly, gain-of-function mutations in the single Drosophila JAK homologue, Hopscotch, result in haemocyte neoplasia, inappropriate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
2
5
0
Order By: Relevance
“…First, the transcription factor Stat92E was found to be a necessary element downstream of JAK, independent of its role in preventing expansion of the cortical zone in wild-type conditions. This result concurs with previous publications showing that phosphorylation of Stat92E in JAK Tum-l haemocytes is required for the formation of melanotic tumours (Bausek and Zeidler, 2014; Remillieux-Leschelle et al, 2002; Sorrentino et al, 2004). We speculate that Stat92E regulates a set of genes in wild-type conditions that prevent the expansion of the pxn+ population, and that these genes are different from those regulated upon JAK phosphorylation, which might be involved in dysplastic growth.…”
Section: Discussionsupporting
confidence: 93%
“…First, the transcription factor Stat92E was found to be a necessary element downstream of JAK, independent of its role in preventing expansion of the cortical zone in wild-type conditions. This result concurs with previous publications showing that phosphorylation of Stat92E in JAK Tum-l haemocytes is required for the formation of melanotic tumours (Bausek and Zeidler, 2014; Remillieux-Leschelle et al, 2002; Sorrentino et al, 2004). We speculate that Stat92E regulates a set of genes in wild-type conditions that prevent the expansion of the pxn+ population, and that these genes are different from those regulated upon JAK phosphorylation, which might be involved in dysplastic growth.…”
Section: Discussionsupporting
confidence: 93%
“…Both ras RNAi lines were able to mimic the mutant dark red eye color phenotype when driven with the lozenge-Gal4 driver (data not shown), which indicated that the RNAi lines were fully functional. We noticed similar phenotypes after knocking down the raspberry transcript in hemocytes with the msnF9mo-Gal4 and the He-Gal4 drivers similarly to Bausek and Zeidler [ 45 ] after reduction of Ga73B levels in a Hop T42 background. The lower Ga73B gene dose, compared to the wild type pre-tumors, prevented the formation of the tightly bound cell mass and resulted in the formation of loosely associated cell clumps, which were not able to develop and generate the melanized tumors visible in adults.…”
Section: Discussionsupporting
confidence: 72%
“…( g ) Penetrance of melanotic tumors (n > 50). ( h ) Relative expression levels of Jak/Stat downstream targets ( apt ( Starz-Gaiano et al, 2008 ) , CG1572 ( Bina et al, 2010 ) , CG13559 ( Bina et al, 2010 ) , Galphaf ( Gα73b ) ( Bina et al, 2010 ; Bausek and Zeidler, 2014 ) and slbo [ Silver and Montell, 2001 ]) in hemocytes from stage 16 embryo srp(hemo)> gcm GOF . The data are relative to the levels in controls as described in Figure 1f .…”
Section: Resultsmentioning
confidence: 99%
“…To assess the impact of Gcm on the Jak/Stat pathway, we analyzed the levels of expression of down-stream targets of Stat92E upon gcm GOF in hemocytes from stage 16 embryos. Several targets of Stat92E were previously described in S2 cells and in hemocytes: apt ( Starz-Gaiano et al, 2008 ) , CG1572 ( Bina et al, 2010 ) , CG13559 ( Bina et al, 2010 ) , Galphaf ( Gα73b ) ( Bina et al, 2010 ; Bausek and Zeidler, 2014 ) and slbo ( Silver and Montell, 2001 ). The over-expression of Gcm significantly reduces the levels of expression of these genes ( Figure 2h ), suggesting that Gcm inhibits the Jak/Stat pathway upon inducing the expression of the inhibitors Ptp61F, Socs36E and Socs44A.…”
Section: Resultsmentioning
confidence: 99%